“MEN AND WOMEN DICTION” IN MODERN INDONESIA POETRY (SOCIOLINGUISTIC-GENDERISTIC STUDIES) - Ganjal Harimansyah (Pusbindiklat - LIPI, 2011)
This paper will describe the results of different studies of language choice between men and women in so phisticated Indonesia poems. This study uses sociolinguistics-genderistics paradigm which states that the gender differences in language choice is not only describing what is commonly accepted as a fact that is reflected in the text, but also what is behind the text. This study uses a qualitative approach method and the results of descriptive data in the form of text or writing literary genre of poetry. The data were obtained by using sampling techniques. This study deals only with the poems of Indonesia in the period 1990–2000’s with a comparison of the poems of Indonesia in the period 1970–1980’s. In this study, the language of poem considered as an aspect which forms and express a direct expression and attitude of speakers with their own nuances that cannot be separated from ideological issues and the application of linguistic variations in language reproductive men and women.